Putusan Pengadilan Dalam Memutuskan Perkara No. 0017/Pdt.G/2013/Pa.Lwb Tentang Disahkannya Perkawinan Siri - Tessa Pritama Eda; Weny Almoravid Dungga; Dolot Alhasni Bakung (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
Tessa Pritama Eda, Nim: 1011419034, with the title Analysis of Court Decisions in Deciding Cases Number: 0017/Pdt. G/2013/Pa.Lwb Regarding Legalization of Siri Marriage. Advisor I Mr. Dr. Weni Almoravid Dungga, S.H., M.H and Advisor II Mr. Dolot Alhasni Bakung, S.H., M.H. The purpose of this study is to find out the legal protection for unregistered marriages and secondly to find out the court's decision in deciding case number: 0017/Pdt.G/2013/Pa.Lwb regarding the legalization of unregistered marriages. The method used in this research is normative. The result of legal protection for unregistered marriages is that unregistered marriages obtain legality from the State if they fulfill predetermined conditions, such as marrying according to religion, then obtain the consent of the first wife as evidenced by a permit, and also for reasons of paperwork. child. But here on the other hand, betel marriage can also be entered into a criminal offense.The decision of the supreme court granted the respondent's request to obtain a marriage certificate, on the grounds that it was in their administrative interests and that of the children, also because the marriage had been carried out in an Islamic manner and had fulfilled all the requirements, and the most important reason was that the marriage had been approved by the first wife.